Fiscal Decentralization Effect on Financial Performance: Mediated by Size and Moderated by Audit Opinion in Lampung Province - Eka Ningsih Puji Rahayu; Rudy Badrudin (Telaah Bisnis, 2019)
Abstract This research aims to examine the effect of fiscal decentralization on financial performance by adding government size as the mediator variable and audit opinion as the moderator variable of counties and cities in Lampung Province. Lampung Province is the center of economic mobility in South of Sumatera Island so it can impact well to regional autonomy implementation and has the best financial statements (an unqualified opinion) in Sumatra Island (47.5%). This research was conducted in 13 counties and 2 cities in 2010-2013 for the objective to see the regional autonomy implementation started in one decade. The examination of hypothesis used to Partial Least Square with the significant of decision-making <0.10. The results show that fiscal decentralization gives the positive and significant effect to financial performance but non-significant effect to government size; government size gives the positive and non-significant effect to finance performance; and fiscal decentralization gives the positive and non-significant effect to finance performance with the audit opinion as the moderator variable.